EMPOWERMENT OF THE ROLE OF NUTRIENTS IN CHECKING FOOD SAFETY ACCORDING TO QUALITY AND BALANCED NUTRITION AT LUBUK PAKAM GRANDMED HOSPITAL - Delita Br Panjaitan; Fadlilah Widyaningsih (JURNAL PENGMAS KESTRA (JPK), 2022)
The food service service in the hospital is a very important part because it is the main key in the healing process of patients who are being treated at the hospital. This service aims to fulfill and ensure that the safety of the food to be served to patients is in accordance with quality and balanced nutrition. This research was conducted by conducting pre and post tests to see whether there was an increase in the understanding of food ingredient supervision or not about quality and balanced nutrition in hospitals. The implementation time of this activity was carried out for 1 week with a total of four meetings. Based on this socialization activity, the role of nutritionists in conducting food supervision according to quality and balanced nutrition has increased in terms of food supervision.